PERFORMANCE OF LUPON IN BARANGAY MANDARAGAT, PUERTO PRINCESA CITY - Maribel D. Limsa; Cynthia A. Tucay (European Journal of Humanities and Educational Advancements, 2024)
Lupon or Lupong Tagapamayapa is a body organized in every barangay to dispense the Katarungang Pambarangay activities of a barangay. Hence, this study was conducted to determine the performance of Lupon using the descriptive research design gathered through survey questionnaires from 18 Lupon members and analyzed using frequency counts, means, and percentages. The study revealed that the performance of the Lupon in barangay was outstanding. Moreover, half of the respondents acknowledged that they lack training in supervising grievances/ conflict brought to the barangay. Hence, majority of them expressed that among the strategies to address the challenges is to have a conduct of in-service training for the Lupon members